Dissolved organic matter in Chascomús Pond (Argentina) : Influence of calcium carbonate on humic acid concentration - Conzonno, Víctor Hugo (1995)
Water chemistry of the Chascomus Pond (Province of Buenos Aires, Argentina) was studied during a year characterized by low precipitation. Supersaturation of calcium carbonate up to a calcite saturation index of about 20 in spring and summer was observed, together with a diminution of the concentration of dissolved organic matter, in particular humic substances (HS). These results suggested an adsorption between organic matter and calcium carbonate which should influence the growth of calcium carbonate crystals. A preferential removal of higher molecular weight HS was observed by gel permeation chromatography experiments.